2012
DOI: 10.1111/j.1365-2524.2012.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of healthcare support workers in providing palliative and end-of-life care in the community: a systematic literature review

Abstract: Despite the widespread use of Health Care Support Workers (HCSWs) in providing palliative and end‐of‐life care, there is little information available about their contributions towards supporting patients who want to be cared for at home or to die at home. Between January and April 2011, a systematic review was conducted to address two questions: (i) What particular tasks/roles do HCSWs perform when caring for people at the end of life and their families to comply with their desire to remain at home?; (ii) What… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 28 publications
5
95
1
2
Order By: Relevance
“…All staff, whatever their role in EoL care, need to be adequately trained and supported to fulfil their role. 72 …”
Section: Symptom Controlmentioning
confidence: 99%
“…All staff, whatever their role in EoL care, need to be adequately trained and supported to fulfil their role. 72 …”
Section: Symptom Controlmentioning
confidence: 99%
“…A recent systematic literature review of the role of HCAs in providing palliative and end-of-life care in the community has identified that the provision of emotional support is a key aspect of their role (Herber & Johnston 2013). Originally defined by Hochschild (1983) as 'the management of feeling to create a publicly observable facial and bodily display,' (Hochschild, 1983, p.7) the concept of emotional labour has been applied to nursing (Bartram et al 2012;Gray 2009;Hayward & Tuckey 2011;James 1992;Schell & Kayser-Jones 2007;Skilbeck & Payne 2003;Smith 1992;Yang & Chang 2008) in general, and more specifically to HCAs involved in community palliative care work (Munday 2007;Ferguson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Papers included studies from Israel (Ben-Arie & Lecovich, 2014), Japan (Igarashi et al, 2015), United States (US) Riesenbeck et al 2015;Butler, 2009), Canada (Morgan et al 2016), Belgium (Roelands et al 2005) and the UK (Dawson et al 2015;Devlin & McIlfatrick, 2009;Ryan et al 2004;Herber & Johnston, 2013) …”
Section: Data Synthesismentioning
confidence: 99%
“…Despite a total of 12 articles exploring the impact on homecare workers providing care for people with dementia or end of life care, few explored the subjective emotional impact of this work (Devlin & McIlfatrick, 2009;Herber & Johnston, 2013).…”
Section: B Emotional Labourmentioning
confidence: 99%